Pengelolaan Keuangan Desa Dalam Meningkatkan Kesejahteraan Masyarakat di Desa Tinting Kecamatan Sarolangun - Yanni Rahman; Mulia Inda Purwati; Kiki Helencia (Jurnal Kajian dan Penalaran Ilmu Manajemen, 2026)
This study aims to determine the village financial management of Tinting Village, Sarolangun Subdistrict, in improving community welfare and to identify its supporting and inhibiting factors. This research uses a descriptive qualitative approach with data collection techniques through interviews and documentation. The informants in this study were the village secretary, village treasurer, and the Village Activity Implementation Team (TPKAD). Data analysis was conducted through data reduction, data display, and conclusion drawing. The results show that the financial management of Tinting Village has been implemented through planning, implementation, administration, reporting, and accountability stages. However, it has not been fully optimal in improving community welfare, as it is still dominated by infrastructure development rather than community economic empowerment programs. The supporting factors include clear regulations, cooperation among village officials, and community participation. Meanwhile, the inhibiting factors consist of limited human resources of village officials, low community understanding, and limited budget for empowerment programs